2010
DOI: 10.1188/10.cjon.765-770
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction With Telehealth for Cancer Support Groups in Rural American Indian and Alaska Native Communities

Abstract: A descriptive study was conducted to determine the information needs of American Indian (AI) and Alaska Native (AN) cancer survivors and assess satisfaction with and acceptability of telehealth support group services for cancer survivors in AI and AN rural communities. AI and AN cancer survivors were asked to complete the Telehealth Satisfaction Survey and two open-ended questions, one regarding information needs and one seeking comments and suggestions about cancer support group meetings. Thirty-two surveys w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 27 publications
2
81
0
Order By: Relevance
“…Overall, the participants very satisfied with the integrated community-based telehealth facilities of this rural township. These results were consistent with that presented in Doorenbos et al [13]. The findings suggested that integrated community-based telehealth has been seen as a viable way to facilitate residents to access care and support services in rural communities.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Overall, the participants very satisfied with the integrated community-based telehealth facilities of this rural township. These results were consistent with that presented in Doorenbos et al [13]. The findings suggested that integrated community-based telehealth has been seen as a viable way to facilitate residents to access care and support services in rural communities.…”
Section: Discussionsupporting
confidence: 83%
“…In synchronous systems, videoconferencing provides a patient and health care provider at either end with interactive clinical encounter via a live telecommunication linkage. Some studies have demonstrated that videoconferencing was a viable method for facilitating cancer support groups to rural communities [13]. On the other hand, asynchronous systems involve the collection and electronic storage of personal health record (PHR; e.g.…”
Section: Integrated Community-based Telehealthmentioning
confidence: 99%
“…The refined prostate cancer education program includes updated content formatted for more innovative and widespread dissemination via videoconference broadcasting to ensure that AA men and women are receiving plain language, culturally appropriate, and targeted prostate cancer information that will allow men to make informed decisions about screening, treatment, and participation in cancer research. Video-based teleconferencing is considered a an effective method for health promotion initiatives and interventions including those for smoking cessation [23], stroke management [24], breastfeeding support [25], and cancer education [26]. Additionally, video-based teleconferencing can be especially advantageous to rural communities that would not otherwise have easy access to relevant and timely health information [26].…”
Section: Introductionmentioning
confidence: 99%
“…Video-based teleconferencing is considered a an effective method for health promotion initiatives and interventions including those for smoking cessation [23], stroke management [24], breastfeeding support [25], and cancer education [26]. Additionally, video-based teleconferencing can be especially advantageous to rural communities that would not otherwise have easy access to relevant and timely health information [26]. The refined program was delivered in person at one central location in the state and the videoconference from the central location was broadcasted at two additional locations across the state with the assistance of additional community partners.…”
Section: Introductionmentioning
confidence: 99%
“…22 Between August 2007 and December 2008, the NPCCTN's healthcare providers' education series offered sessions on survivorship care, end-of-life issues, cancer care for children, pharmacological pain management interventions, and reviews of specific types of cancer. From February 2008 through September 2009, the NPCCTN offered a monthly support group meeting for cancer survivors that incorporated an educational presentation on a variety of issues related to survivorship, a question and answer session, and an opportunity for cancer survivors across the region to interact via video teleconference.…”
Section: Resultsmentioning
confidence: 99%